Development of dental resin luting agents based on Bis-EMA4: bond strength evaluation (eXPRESS Polymer Letters)
The aim of this study was to investigate the influence of incorporating Bis-EMA4 monomer into experimental Bis-GMA/TEGDMA-based resin luting agents on the bond strength to dentin. Seven mixtures were prepared with the following ratios (wt%) of Bis-GMA/TEGDMA/Bis-EMA4: 50/50/0, 50/30/20, 50/10/40, 50/0/50, 30/10/60, 10/10/80 and 0/0/100. Camphorquinone (0.4 wt%), N,N-dimethyl-p-toluidine (0.8 wt%) and hydroquinone (0.2 wt%) were dissolved in each mixture, which was loaded with silanated strontium glass fillers to a constant content of 60 wt%. Bond strength was evaluated by microshear testing (n = 10) on bovine dentin. Data were submitted to Analysis of Variance (p<0.05). Modes of failure were classified under magnification (200×). Bond strength means (MPa), respective to each agent, were: 19.4, 19.8, 20.0, 19.1, 16.8, 18.7 and 17.8. No significant differences were detected among groups. Mixed failures were generally predominant for all materials. In conclusion, the addition of Bis-EMA4 presented no significant influence on the bond strength of the experimental resin luting agents to dentin.